Data, doppler, or depth of knowledge: How do television stations differentiate local weather? - Daniels, George; Loggins, Ginger (My University, 2011)
Although weather coverage has never received extensive research, previous studies have investigated the importance of weather to viewers and to television station branding. Additionally, such individual features of weather reports like accuracy have been investigated, but no researcher has apparently examined the overall content of day-to-day local televised weathercasts. This content analysis of weathercasts in five medium to large Southern U.S. markets sheds light on the ways stations differentiate themselves through their weathercasts’ content. It found that so many stations use radar or claims of accuracy to differentiate themselves that the techniques do not result in product differentiation. Other methods, by themselves or combined with accuracy and radar, may better differentiate weathercasts.
Keywords: Televised weathercasts; Local weather; Television stations; Weather forecasts